ENTREPRENEURIAL ECOSYSTEMS: A CONFIGURATIONAL RESEARCH APPROACH - Stefenon, Rafael (2023)
The entrepreneurial ecosystem approach has emerged as a framework capable of providing a systemic understanding of entrepreneurship. Considering that entrepreneurial ecosystems admit different configurations, this article aims to stimulate a reflection on the application of the configurational approach in the analysis of entrepreneurial ecosystems. An analysis model based on six dimensions of entrepreneurial ecosystems is indicated: geographic breadth, sectorial diversity, mode of governance, degree of maturity, innovative effort, and environmental munificence. This proposal is justified by indicating a possibility for a more subtle and rigorous understanding of entrepreneurial ecosystems, allowing for more precise and reliable policy recommendations for the creation and strengthening of entrepreneurial ecosystems.